2012
DOI: 10.1186/1750-1172-7-47
|View full text |Cite
|
Sign up to set email alerts
|

The treatable intellectual disability APP www.treatable-id.org: A digital tool to enhance diagnosis & care for rare diseases

Abstract: BackgroundIntellectual disability (ID) is a devastating and frequent condition, affecting 2-3% of the population worldwide. Early recognition of treatable underlying conditions drastically improves health outcomes and decreases burdens to patients, families and society. Our systematic literature review identified 81 such inborn errors of metabolism, which present with ID as a prominent feature and are amenable to causal therapy. The WebAPP translates this knowledge of rare diseases into a diagnostic tool and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
1
33
0
3
Order By: Relevance
“…After reading the abstracts it was found that, even though one of the terms in the educational sphere appeared in the title, the content of the paper was medical. Some were related to the training of medical and healthcare staff in the field of RDs (Jinnah, 2011;Van Karnebeek et al, 2012). Others had to do with university studies and knowledge, as in the case -for example -of the paper by Cismondi et al (2015), which addressed the educational issues associated with particular rare diseases in the curricula of Health Sciences and Professional Training Programs.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the abstracts it was found that, even though one of the terms in the educational sphere appeared in the title, the content of the paper was medical. Some were related to the training of medical and healthcare staff in the field of RDs (Jinnah, 2011;Van Karnebeek et al, 2012). Others had to do with university studies and knowledge, as in the case -for example -of the paper by Cismondi et al (2015), which addressed the educational issues associated with particular rare diseases in the curricula of Health Sciences and Professional Training Programs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, new digital and social media offer new opportunities to facilitate the diagnostic journey. Addressing the need for timely diagnosis a Dutch group developed a mobile application (App) for earlier diagnosis of treatable diseases resulting in psychomotor delay [31]. Such approaches illustrate the benefits of today's technology which was successfully used in the current project.…”
Section: Discussionmentioning
confidence: 99%
“…1b), and is endorsed by the rare disease community [17] The app allows for the creation of a list of differential diagnosis according to symptoms and signs of the single treatable IDD and thus facilitates, particularly the second tier of the protocol which is based on an astute clinical differential diagnosis.…”
Section: The Tide Diagnostic Algorithm and Appmentioning
confidence: 99%
“…The application of the TIDE protocol in conjunction with TIDE app [14,15,17] would have lowered the total cost for each of these patients to a base of $527.97 CAD, plus the expense of individual second-tier tests on a case-by-case basis.…”
Section: Costsmentioning
confidence: 99%